Comparison of Respiratory Pathogens in Children With Lower Respiratory Tract Infections Before and During the COVID-19 Pandemic in Shanghai, China - Xu, Menghua; Liu, Pengcheng; Su, Liyun; Cao, Lingfeng; Zhong, Huaqing; Lu, Lijuan; Jia, Ran; Xu, Jin (Frontiers in Pediatrics, 2022)
Objectives: This study aimed to assess the impact of COVID-19 on the prevalence of respiratory pathogens among hospitalized children with lower respiratory tract infections (LTRIs) in Shanghai. Methods: Respiratory specimens were collected from children with LTRIs in Children’s Hospital of Fudan University from February 2019 to January 2021 and common respiratory pathogens were detected using multiplex PCR. The data of 13 respiratory pathogens were analyzed and compared between the year of 2020 (from February 2020 to January 2021) and 2019 (from February 2019 to January 2020). Results: A total of 1049 patients were enrolled, including 417 patients in 2019 and 632 patients in 2020. In 2020, 27.53% of patients were tested positive for at least one pathogens, which was significantly lower than that in 2019 (78.66%). The top three pathogens were Mp, ADV and RV in 2019, whereas RV, RSV and PIV were the predominant ones in 2020. The positive rates of Mp, ADV, RV, PIV, InfB, H3N2 and H1N1 were significantly decreased in 2020. RV was the most detectable respiratory pathogen in 2020, and become the most frequent pathogen in all five age groups. PIV had a high prevalence from October to December 2020 which was even higher than that in 2019. InfA was not detected in 2020. Co-infection was significantly less frequent in 2020. Conclusions: The public health interventions aiming to eliminate COVID-19 have great impact on the prevalence of common respiratory pathogens. The prevalence of RV and PIV reminds us a possible resurgence of some pathogens.